Filhas de Eva como anjos sobre a Terra: A pia união das filhas de Maria em Limoeiro-CE (1915 - 1945). - Andrade, Maria Lucelia de (2008)
The present research analyzes the Pious Union the Daughters of Mary, religious brotherhood of single women catholics in Limoeiro, Ceara (1915 - 1945). Aiming to form feminine models of moral behavior, this brotherhood was place of disciplines, norm and social distinction. The study examines practical of reading of the associates Pious Union, articulating dimensions: devotional, exemplary, informative, educational, entertainment and moralizing. Such practices are centrally prescribed in Catholic journalism, classifying and distinguishing between the good and the bad readings. The language of cinema is also broached in the study. The Library of the Pious Union participates of this research, forming a documentary corpus that includes pious and exemplary books and novels. The research still considers the performance of the Daughters of Mary in the educational field as teachers and as catechists in the Catholic proselytism.